THE ANALOGOUS RESULTS OF A STUDY ON REGULAR IRREDUCABLE ALGEBRAIC MONOIDS - Rakshit, Madhuchanda; Kumar, Vinod (International Journal of Psychosocial Rehabilitation, 2021)
This paper aims to introduce various ideas related to irreducible algebraic monoids in a very concise manner. The geometry of algebraic monoids is investigated. We show that an irreducible algebraic monoid’s group of invertible elements is an algebraic group open in the monoid. This theory combines algebraic groups, green class topology, Grassmann manifolds, and natural monoidal structure in a natural way. In mathematics, it is a very busy and fruitful research area. Natural bundle structures on the space of idempotents, as well as the various Green classes, were also discussed.